Long-Chain Hydrocarbons (C21, C24, and C31) Released by Bacillus sp. MH778713 Break Dormancy of Mesquite Seeds Subjected to Chromium Stress - Ramírez, Verónica; Munive, José-Antonio; Cortes, Luis; Muñoz-Rojas, Jesús; Portillo, Roberto; Baez, Antonino (Frontiers in Microbiology, 2020)
Volatile organic compounds (VOCs) produced by rhizobacteria have been proven to stimulate plant growth during germination and seedling stages. However, the modulating effect of bacterial volatiles on the germination of seeds subjected to heavy metal stress is scarcely studied. In this work, the ability of volatiles released by Bacillus sp. MH778713 to induce seed dormancy breakage in Prosopis laevigata and Arabidopsis thaliana seeds were examined. The minimal inhibitory concentration of chromium (Cr) VI that prevents seed germination of P. laevigata and A. thaliana on water-Cr-agar plates was 2500 and 100 mg L-1, respectively. Remarkably, partitioned Petri-dish co-cultivation of Bacillus sp. MH778713 and plant seeds under Cr-stress showed the beneficial effect of volatiles emitted by Bacillus sp. MH778713, helping plant seeds to overcome Cr-stress. Among the metabolites emitted by Bacillus sp. MH778713, octadecane, heneicosane, 2,4-di-tert-butylphenol, hexadecane, eicosane, octacosane, and tetratriacontane were the most abundant. To confirm that these long-chain compounds produced by Bacillus sp. MH778713 could be responsible for the seed dormancy breakage, high pure organic compounds (2,4-di-tert-butylphenol, heneicosane, hentriacontane, and tetracosane) were used directly in germination assays of P. laevigata and A. thaliana seeds instead of volatiles emitted by Bacillus sp. MH778713. All organic compounds allowed Prosopis and Arabidopsis seeds to overcome Cr-toxicity and germinate. The results of this study provide new insight into the role of long-chain bacterial compounds produced by Bacillus sp. MH778713 as triggers of seed abiotic stress tolerance, surmounting chromium stress and stimulating seedling development.